Peran Pengelolaan Kearsipan dalam Memediasi Pengaruh Pelatihan Arsip, Kompetensi Arsip, dan Sarana Prasarana Arsip, terhadap Efektivitas Kerja Pegawai Tata Usaha - Pertiwi, Anggita Gilang; Ismiyati, Ismiyati (Universitas Negeri Semarang, 2021)
The purpose of this study was to determine the role of archival management in mediating the effect of training, archives, archive officer competence, and archival infrastructure on the work effectiveness of administrative employees at SMK-se in Batang Regency. The results showed that (1) archiving training had a positive and significant effect on the management of SMK archives in Batang Regency, 2) Archival officer competence had an effect on the management of SMK archives in Batang Regency, 3) Archive facilities and infrastructure had a positive and significant impact on the management of SMK archives in Batang Regency. Batang, 4) Archive management has an effect on the work effectiveness of administrative employees of SMK in Batang Regency, 5) Archival training has a positive and significant effect on the work effectiveness of administrative employees in SMK in Batang Regency. 6) The competence of archive officers has a positive and significant effect on the work effectiveness of administrative employees in SMK in Batang Regency, 7) Archival facilities and infrastructure have a positive and significant effect on the work effectiveness of administrative employees in SMK in Batang Regency, 8) Training and employee work effectiveness administration in SMK in Batang Regency through archive management is proven in this study, 9) archive officers affect the work effectiveness of administrative employees in SMK in Batang Regency through archive management proven in this study, 10) Facilities and infrastructure affect the work effectiveness of administrative employees business in SMK in Batang Regency through archive management.